MENINGKATKAN PERAN MASYARAKAT DALAM PENCEGAHAN COVID 19 DI PASAR PETERONGAN KAB.JOMBANG - Sylvie Puspita; Enny Puspita; Hany Puspita Aryani; Semi Naim (Bajang Institute, 2022)
The market is one of the places that can be a transmission of Covid-19 transmission. This is because the process of interaction and transactions that occur in the market facilitates the transmission of distribution. One way to break the chain of transmission is by implementing Covid-19 prevention behavior. The problem that occurs in the field is the poor behavior of traditional market traders who have not used masks consistently and the difficulty of keeping a distance has caused the Covid-19 transmission rate in the market to be one of the places that are prone to Covid-19 transmission. Based on Sariagri's news as of August 2020, the average Covid cluster is dominated by traditional market clusters, both those in the Peterongan Market and the Mojoagung Market. Every day, the addition of COVID-19 cases in Jombang, can reach 5 to 8 cases. The method used in the service goes through three processes, namely preparation of activities, implementation of health education and closing or evaluation. the implementation of community service involves 40 peteronggan market traders. There is a change in people's knowledge from not good enough to good and there is a change in the implementation of hand washing traders.